A new neuropsychological tool for simultaneous reading and executive functions assessment: initial psychometric properties - de Oliveira, Vinícius Figueiredo; Vial-Martins, Jéssica; Pinto, André Luiz de Carvalho Braule; Fonseca, Rochele Paz; Malloy-Diniz, Leandro Fernandes (Frontiers in Psychology, 2024)
The development of reading and complex executive functions is fundamental for achieving social, academic, and professional success. So far, there is no single neuropsychological instrument that comprehensively assesses the domains of inhibitory control, cognitive flexibility, working memory, and reading comprehension. To assess executive functions related to reading, the "Assessment of Reading and Executive Functions" (AREF) was developed. In this study, we show initial evidence of validity and reliability for four subtests -Graphophonological-Semantic Flexibility, Inhibitory Control, Flexibility, and Working Memory. A total of 93 students from 4th to 9th grade, aged 8-14, in public (n = 61) and private (n = 32) schools were evaluated. The results of the AREF subtests demonstrated significant positive correlations with measures of reading (ranging from 0.339 to 0.367) and executive functions (ranging from 0.209 to 0.396). Regarding evidence of reliability, the internal consistency of the tasks was low for Graphophonological-Semantic Flexibility (Cronbach's α = 0.566), moderate for Inhibitory Control and Flexibility (Cronbach's α = 0.768), and high for Working Memory (Cronbach's α = 0.881). It is expected that this new neuropsychological test will contribute to the assessment of reading skills and executive functions, assisting in directing clinical and educational interventions for individuals with and without neurodevelopmental disorders.